INSTRUCTOR AND STUDENT EXPERIENCES OF MIGRATING TO ONLINE LANGUAGE INSTRUCTION - Williams, Gwendolyn M.; Diamond, Mary S.; Yoo, Hyeon-Jean (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This article considers the similarities and differences between two constructivist studies examining the experiences of emergency remote teaching and learning English. One project explored instructors’ descriptions of facilitating the transition from in-person to online instruction during the COVID-19 pandemic. The second investigation analyzed the experiences of multilingual students as they made the transition from in-person to online. The first study elicited data through a Qualtrics open-ended questionnaire, while the research on students’ experiences examined student writing samples from their coursework. After the researchers coded both data sets through thematic analysis (Braun & Clarke, 2022), they collaborated to ensure interrater reliability (Belur et al., 2021). Results indicated that the nature of their concerns differed based on their role as the course consumer versus the course creator. Instructors struggled more with transforming their in-person content to an online context, while the students struggled with accessing and participating in the online learning experience. Accordingly, the authors recommend that both instructors and students receive instruction on how to engage in online learning. Additionally, instructors should build redundancy into their online courses so that students have multiple means of accessing and responding to instructional content.